Penggunaan Media Gambar pada Mata Pelajaran IPA Materi Ciri-Ciri dan Kebutuhan Makhluk Hidup Dapat Meningkatkan Hasil Belajar Siswa Kelas III SDN. No. 031/ XI Kampung Dalam Tahun 2016/2017 - Erzos Maidar (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
This study aims to improve learning outcomes of third grade students in science subjects, especially on the material characteristics and needs of living things in the SDN. No. 031/XI Kampung Dalam year 2016/2017 image media. The type of research conducted is classroom action research conducted in two cycles (Cycle I and Cycle II) and each cycle consists of two meetings with four activities, namely planning, implementation, observation, and reflection. This research involved 27 students of third grade at SDN. No. 031/XI Kampung Dalam, Hamparan Rawang Subdistrict, Sungai Penuh City, Jambi Province. The study was conducted from July to November of 2016. Data were collected through objective test and observation. Data was processed by descriptive analysis and simple statistical test. The results showed that the use of image media can improve student learning outcomes. This increase can be seen from the increase of the average score and the percentage of students' learning mastery. The average score of students before action was 50,74 increased to 64,07 in Cycle I, and increased again to 74,81 in Cycle II. Similarly, the percentage of learning mastery. Percentage mastery of students before action is given 48,15% increased to 62,96% in Cycle I and increased again to 85,19% in Cycle II. Thus, the use of image media can improve the learning outcomes of third grade students in science subjects, especially on the material characteristics and needs of living things in the SDN. No. 031/XI Kampung Dalam year 2016/2017.